2001
DOI: 10.1046/j.1467-0658.2001.00114.x
|View full text |Cite
|
Sign up to set email alerts
|

Resilience programs for children in disaster

Abstract: ObjectivesThe long-term objectives of the International Resilience Research Project (IRRP), were to indicate: a. how children become resilient and how service providers incorporate the promotion of resilience into their programs. The intermediary objectives were to: (1) indicate how resilience is promoted in different cultures with different age groups; (2) identify what resilience behaviors deal with and overcome the potentially damaging aspects of adversities and disasters; and (3) identify the role of adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0
13

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 2 publications
(1 reference statement)
2
27
0
13
Order By: Relevance
“…In line with this finding, other studies have shown that mental health is one of the most important components of children’s resilience in disasters that most scholars have emphasized. Recent studies have also emphasized the importance of the psychological component as a factor that affects children’s resilience (Fu, 2012; Grotberg, 2001; Massad et al, 2009; Masten, 2014; Wang, Zhang, & Zimmerman, 2015). Other studies have identified psychological, emotional, cognitive, and mental components as individual and personality traits or characteristics (Jacelon, 1997; Wagnild & Young, 1993), which can determine the capacity of children in disasters, in line with the current study.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this finding, other studies have shown that mental health is one of the most important components of children’s resilience in disasters that most scholars have emphasized. Recent studies have also emphasized the importance of the psychological component as a factor that affects children’s resilience (Fu, 2012; Grotberg, 2001; Massad et al, 2009; Masten, 2014; Wang, Zhang, & Zimmerman, 2015). Other studies have identified psychological, emotional, cognitive, and mental components as individual and personality traits or characteristics (Jacelon, 1997; Wagnild & Young, 1993), which can determine the capacity of children in disasters, in line with the current study.…”
Section: Discussionmentioning
confidence: 99%
“…"Eğitimde dirençlilik-educational resiliency" (Kitano ve Lewis, 2005;Morales, 2014;Wang ve Gordon, 1994) ya da "akademik dirençlilik-academic resiliency" (Erberber vd., 2015;Grotberg, 2001) dirençli öğrenciler için kullanılan farklı iki tanımlamadır. Ancak tanımların detaylarına bakıldığında dirençli öğrencilerin, sahip oldukları zor şartlara rağmen başarılı olan bireyler olarak tanımlandığı görülmektedir.…”
Section: Introductionunclassified
“…Em suma, a resiliência pode ser entendida como o processo que possibilita transformar uma situação traumática e dolorosa numa possibilidade de aprendizagem e de crescimento, ou, ainda melhor, o processo que facilita o combate da adversidade percebida e causadora de danos, possibilitando ao sujeito sair dela fortalecido (Grotberg, 2001). Ou, nas palavras de Assis, Avanci, Pesce e Deslandes (2006), resiliência significa a capacidade de "encontrar forças para transformar intempéries em perspectivas" (p. 19).…”
Section: Introductionunclassified
“…Alguns autores consideram a existência de quatro fatores principais de proteção: (a) relações efetivas e significativas com adultos que possam oferecer apoio, incentivo e orientação, (b) estabelecimento de relações saudáveis com o grupo de pares, (c) desenvolvimento de estratégias eficazes nas soluções de problemas, e (d) inserção ou acesso a comunidades que se preocupam com o bem comum de seus membros (Dumont & Provost, 1999;Grotberg, 2001;Tiet et al, 1998).…”
Section: Introductionunclassified